2013
DOI: 10.1101/gr.154773.113
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric chimpanzees and gorillas harbor convergent gut microbial communities

Abstract: The gut microbial communities within great apes have been shown to reflect the phylogenetic history of their hosts, indicating codiversification between great apes and their gut microbiota over evolutionary timescales. But because the great apes examined to date represent geographically isolated populations whose diets derive from different sources, it is unclear whether this pattern of codiversification has resulted from a long history of coadaptation between microbes and hosts (heritable factors) or from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
166
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(185 citation statements)
references
References 31 publications
18
166
1
Order By: Relevance
“…This result was consistent with the findings for other ruminant species, including Bovinae, Cervidae, Caprinae, Camelidae and Giraffidae (Henderson et al 2015). Moreover, the predominant bacteria in the rumen of red deer were similar to those in elk, white-tailed deer, roe deer, sika deer, reindeer and moose (Gruninger et al 2014;Ishaq and Wright 2014;Li et al 2013;Li et al 2014;Sundset et al 2007). This result suggest an effect on rumen microbiota by host genetics (Moeller et al 2013).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This result was consistent with the findings for other ruminant species, including Bovinae, Cervidae, Caprinae, Camelidae and Giraffidae (Henderson et al 2015). Moreover, the predominant bacteria in the rumen of red deer were similar to those in elk, white-tailed deer, roe deer, sika deer, reindeer and moose (Gruninger et al 2014;Ishaq and Wright 2014;Li et al 2013;Li et al 2014;Sundset et al 2007). This result suggest an effect on rumen microbiota by host genetics (Moeller et al 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, metagenomic analyses in the rumen of Svalbard reindeer and sika deer also suggested that Prevotella spp. plays a potential role in cellulose degradation (Li et al 2013;Pope et al 2012). Indeed, Huws et al (2016) The results also showed that Succiniclasticum spp.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This has been an important area of microbiome research since it was first stated that host phylogeny was the main factor explaining gut microbiome composition in different primate species (Ochman et al, 2010;Yildirim et al, 2010). Since then, further evidence has highlighted a more prominent role of diet and digestive modularity in defining gut microbiome composition in primates (Amato et al, 2014b;Gomez et al, 2015;Muegge et al, 2011;Ley et al, 2008;Moeller et al, 2013). However, for the first time, we present inter-species microbiome differences in two different members of the primate order in the context of seasonal dietary variability and microbe-metabolome interactions.…”
Section: Discussionmentioning
confidence: 99%